2015
DOI: 10.5603/ep.2015.0037
|View full text |Cite
|
Sign up to set email alerts
|

Biopsje cienkoigłowe guzków tarczycy pod kontrolą USG — porównanie wydajności próbki za pomocą różnych technik pobierania próbek, rozmiarów igieł, z/bez analizy cytologicznej na miejscu

Abstract: Introduction: The aim of this study was to compare the diagnostic adequacy of thyroid samples obtained by aspiration or capillary biopsy techniques, with 22 or 27 gauge needles, and with or without onsite cytological analysis (OCA). Material and methods: Four hundred patients with thyroid nodules underwent ultrasound (US)-guided fine-needle biopsies. Patients were divided into eight groups according to needle size (22 vs. 27 gauge), biopsy technique (aspiration vs. capillary), and whether or not OCA was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Regarding the unsatisfactory rates, Tanaka et al found that there was no statistical difference between 22 G and 25 G needles [ 19 ]. In terms of adequacy, there was no statistically significant difference between 21 G and 27 G needles [ 8 ], between 22 G and 27 G needles [ 20 ], and among 23 G, 25 G, and 27 G needles [ 21 ]. Therefore, more cellular specimens did not necessarily result in increased diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the unsatisfactory rates, Tanaka et al found that there was no statistical difference between 22 G and 25 G needles [ 19 ]. In terms of adequacy, there was no statistically significant difference between 21 G and 27 G needles [ 8 ], between 22 G and 27 G needles [ 20 ], and among 23 G, 25 G, and 27 G needles [ 21 ]. Therefore, more cellular specimens did not necessarily result in increased diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may influence the representativeness of the samples is the gauge of the needle used. However, there are few and conflicting reports on this topic, so the contribution of the needle gauge to the cytological adequacy remains unclear [10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the procedure, various techniques for thyroid FNA have been proposed, but consensus for the optimal method has not been established. Despite the current advances in all aspects of cancer diagnosis, there are still no uniform standards for which type of FNA needle will allow the best adequacy rate [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the sampling adequacy was related to the needle size, lymph node dimension, and operator's experience etc. (11)(12)(13). The values of FNA and FNC with different needle gauges have been extensively investigated in the previous studies (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%